2019
DOI: 10.1007/s11139-019-00142-3
|View full text |Cite
|
Sign up to set email alerts
|

Universal sums of generalized pentagonal numbers

Abstract: For an integer x, an integer of the form P 5 pxq " 3x 2´x

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…When m = 4, we can deduce that γ 4 = 15 from the Conway-Schneeberger Fifteen Theorem and the fact that the quaternary quadratic form x 2 + 2x 2 + 5x 2 + 5x 2 represents every positive integer except for 15. For m = 5, Ju [14] recently showed that γ 5 = 109. Since each hexagonal number can be written as a It may be natural to ask whether one can consider similar questions with mixed sums of m j -gonal numbers.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…When m = 4, we can deduce that γ 4 = 15 from the Conway-Schneeberger Fifteen Theorem and the fact that the quaternary quadratic form x 2 + 2x 2 + 5x 2 + 5x 2 represents every positive integer except for 15. For m = 5, Ju [14] recently showed that γ 5 = 109. Since each hexagonal number can be written as a It may be natural to ask whether one can consider similar questions with mixed sums of m j -gonal numbers.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“….). Let (b, c, d) be one of the triples (1, 1, 2), (1, 2, 3), (1, 2, 6) and (2,3,4). We show that each n = 0, 1, 2, .…”
mentioning
confidence: 90%
“…contains all nonnegative integers whenever it contains the twelve numbers 1,3,8,9,11,18,19,25,27,43, 98, 109.…”
Section: Introductionmentioning
confidence: 99%
“…A tight universal m-gonal form having minimum 1 is simply called universal. The universal m-gonal forms have been studied by many mathematicians and there are several results on the classification problem (see, for example, [2], [7], [8] and [9]). Note that P 4 pxq " x 2 and the classification of universal diagonal quadratic forms can be easily done by using Conway-Schneeberger 15-Theorem(see [1] and [3]).…”
Section: Introductionmentioning
confidence: 99%